Editorial - Tsednee, Munkhtsetseg (Mongolian Journal of Chemistry, 2024)
Mongolian Journal of Chemistry presents our second issue of 2024. The issue includes 1 mini-review and 5 excellent research articles, reporting their original research results in the fields of biochemistry, phytochemistry, organic synthesis, and material science. In the mini-review, Narayanan and Suseem explored the pharmacological activities of the medicinal plant Ipomoea staphylina. Sarwade et al. synthesized metal-ligand-based agents with improved biological activities; Radhi et al. report the surface modification of banana peels for the absorption of green dye; Vo et al. prepared a protein hydrolysate with iron-binding, emulsification, and foaming capacities, from a featherback skin; Mishra et al. developed a negatrode material with enhanced energy storage capacity from a bark tree; and Purevdorj et al. report the effect of long-term grazing stress in phytochemical contents of pasture plants. A cover image of the issue is selected from Mishra et al. illustrating the physicochemical characterization of their developed negatrode materials, BZAC-4, BZAC-6, and BZAC-8.